Cord Blood Serum Zinc Levels and the Intrauterine Growth Status in Preterm Neonates - Anna, Annisa Trie; Alasiry, Ema; Febriani, A. Dwi Bahagia; Budi, Setia; Maddepungeng, Martira; Artati, Ratna Dewi (International Journal of Child Health and Nutrition, 2024)
Background: The risk of death is higher if the SGA baby is accompanied by prematurity. Intrauterine growth is considered to have an important role in the occurrence of premature birth and SGA, so many recent studies are trying to find that can support intrauterine growth, one of which is research on the role of the micronutrient zinc, which is a trace element that the body cannot produce. Zinc is an essential micronutrient for organ development and growth. Zinc plays a role in DNA synthesis and the signaling pathway of the IGF-1 receptor. Umbilical cord blood serum zinc levels can reflect intrauterine zinc status, indicating maternal zinc supply to the fetus. Objectives: To assess the relationship between cord blood serum zinc levels and intrauterine growth status in pretermneonates. Methods: This research is an observational study with a cross-sectional approach. The sample for this study was 85 pretermneonates, consisting of 53 neonates with AGA (appropriate for gestational age) and 32 neonates with SGA (small for gestational age). A cord blood sample was collected immediately after birth, and zinc levels were determined by the atomic absorption spectrophotometer method. Results: The median serum zinc levels of the SGA and AGA groups were 41.87 µg/dl (20.43 - 56.04 µg/dl) and 52.12 µg/dl (35.54 - 62.46 µg/dl), respectively, and the difference between the two groups was found to be statistically significant. Conclusion: There was a relationship between cord blood serum zinc levels and the intrauterine growth status of pretermneonates.